Antifungal stewardship in critical care: Implementing a diagnostics-driven care pathway in the management of invasive candidiasis. Issue 2 (June 2020) - Hare, D.; Coates, C.; Kelly, M.; Cottrell, E.; Connolly, E.; Muldoon, E.G.; O' Connell, B.; Rogers, T.R.; Talento, A.F.
Summary: Background: Invasive candidiasis (IC) is the most common invasive fungal disease in patients admitted to critical care and is associated with high mortality rates. Diagnosis can be delayed by the poor sensitivity of culture-based methods, leading to unnecessary use of empirical antifungal therapy (EAFT). The fungal biomarker (1–3)-β-d-glucan (BDG) has been shown to aid in the diagnosis of IC in critical care and has been incorporated into antifungal stewardship (AFS) programmes. Aim: To describe our experience using a diagnostics-driven AFS programme incorporating the fungal biomarker BDG, analyse its impact on antifungal therapy (AFT), and gain an improved understanding of the epidemiology of IC in our critical care unit (CrCU). Methods: An AFS care pathway incorporating BDG was introduced in the CrCU in St James's Hospital, Dublin. Following an educational programme, compliance with the pathway was prospectively audited between December 1st, 2017 and July 31 st, 2018. Results and Conclusion: One hundred and nine AFT episodes were included, of which 95 (87%) had a BDG sent. Of those with BDG results available at the time of decision-making, 38 (63%) were managed in accordance with the care pathway. In compliant episodes without IC, median EAFT duration was 5.5 days [IQR 4–7] and no increase in mortality or subsequent IC was observed. Although adopting a diagnostics-driven approach was found to be useful in the cohort of patients with BDG results available, the use of once-weekly BDG testing did not result in an observed reduction in the consumption of anidulafungin, highlighting an important limitation of this approach.